OPTIMALISASI PROGRAM RUTINAN HUBUNGAN MASYARAKAT PADA PT INDONESIA POWER SURALAYA POWER GENERATION UNIT KOTA CILEGON - Titi Stiawati; Iis Nur Annisa (Jurnal Ilmiah Tata Sejuta STIA Mataram, 2023)
The focus of this research is on the routine program of the PR division of PT Indonesia Power Suralaya PGU. Routine programs are activities that are carried out on a daily, daily, or monthly basis. The PR division of PT Indonesia Power has several internal and external routine programs, which have been implemented well. However, in its implementation there are still some obstacles, such as the difference in information obtained between employees of the public relations division. The method used is descriptive qualitative. The purpose of this study is to find out what should be optimized in routine programs so that the obstacles encountered can be overcome properly. The theory used is the performance theory of Agus Dwiyanto (2006) which consists of five variables, but uses only three indicators, namely responsiveness, responsibility. and accountability. The results of this study indicate that the implementation of routine programs in the public relations division is good but there are some things that are not optimal. The responsiveness variable that was carried out was not maximized because there was still misinformation between the employees of the PR division so that internal communication needed to be improved. The responsibility variable is good because of the employee's awareness to work together on other tasks. While the accountability variable is good because the service provided by the employees is quite good, which is able to provide satisfaction for employees of other divisions and external parties of PT Indonesia Power Suralaya PGU.